SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA PENGANCAMAN MELALUI MEDIA ELEKTRONIK BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Maknun, Luil (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2024)
Threatening crimes are very easy to commit, moreover with modern means accessible, very common for someone to threaten someone by pressure, these threats can lead to death. Criminal sanctions against perpetrators of electronic media intimidation are based on Act No. 19 of 2016 on electronic information and transactions and criteria that determine the presence of threats through electronic media. This research uses normative jurisprudential methods, methods that point research to library data, or secondary data through legal foundations and legal comparisons. As regards the form of criminal sanctions for perpetrators of intimidation contained in Article 27 of the Act No. 19 of 2016 on Amendment of the Law No. 11 of 2008 on Electronic Information and Transactions, it is regulated in Article 29 jo. Article 45B of the law No. 11, 2008 on electronic information and transactions as amended by the Act no. 19 from 2016 on amendment to the Act of 11 of 2008.